Exploring how a genetic attribution to disease relates to internalised stigma experiences of Xhosa people with schizophrenia and rheumatic heart disease in South Africa - Matshabane, Olivia Precious (Department of Medicine, 2020)
Advances in genomics research have brought forth a number of psychosocial concerns. In Africa, in particular, one of the concerns relates to the potential impact of genomics research on stigma experienced by specific population groups. Using a mixed-methods approach, this study sought to explore how genetic causal explanation relates to the internalised stigma experiences of a sample of South African Xhosa people with schizophrenia (n= 36) and rheumatic heart disease (n= 46). Additionally, a pilot study was conducted with another sample of schizophrenia (n= 65) and rheumatic heart disease (n= 55) patients to translate and adapt an internalised stigma of mental illness scale into isiXhosa. The aim of the study was operationalised into three research questions, namely; 1. What causal attribution models do Xhosa people with schizophrenia and rheumatic heart disease employ to explain their illness and to what extent do genetic explanations play a role in these causal models? 2. What are the internalised stigma experiences of Xhosa people with schizophrenia and rheumatic heart disease? 3. How do the genetic causal explanations of Xhosa people with schizophrenia and rheumatic heart relate to their internalised stigma experiences, if at all? Through focus-group discussions participants were introduced to non-genetic and genetic causal explanations and then asked a series of open-ended questions eliciting their perceptions of disease causation, genetic causation and the possible implications these perceptions may have on internalised stigma they may have experienced. Next, an internalised stigma of mental illness scale (ISMI) was translated through a mixed-methods translation approach into Xhosa and adapted for use in both disease groups. Insights from this translation were used to gain an understanding of how the Xhosa language supports particular descriptions and conceptualisations of stigma experiences. Psychometric results provided further insights into particularly relevant internalised stigma items for each disease group. Findings from the FGDs and translation process suggested that firstly Xhosa people with schizophrenia and those with rheumatic heart disease have a general understanding of genetics and genetic attribution to disease. Secondly, and not withstanding this knowledge, these participants hold a multitude of disease explanations. In consideration of the alternative causal explanations, and the factors these participants are exposed to, the genetic explanation did not appear to relate to their internalised stigma. While there was evidence of stigma in the two disease groups - schizophrenia patients reporting more stigma than the rheumatic heart disease sample - this stigma was not often related to a genetic attribution of disease. Findings suggest that the link between genetic attribution and stigma is complex. Due to the variable nature of the evidence derived from the study we cannot conclude that a genetic attribution is not related to stigma, however the findings provide clues as to why this is an unlikely implication for Xhosa people in these disease groups. This finding is different to empirical research which has been conducted in North American and European contexts. Although research in Western and European contexts suggests that attributing a disease to genetics may have an impact on disease-stigma, there have been minimal efforts to explore that assumption in the African context. This study, being one of the first to explore that assumption in an African population group, did not find consistent evidence to support it.